The relationship between intercultural interactions and encounters and professional identity of English Language Teachers : a narrative multiple case study before, during, and after a short-term sojourn abroad (2024)
This dissertation explored the influence of intercultural interactions and encounters on the professional identity development of English Language Teachers (ELTs) during short-term sojourns in U.S. summer camps. The study drew on a qualitative narrative inquiry with a multiple-case study design. The research questions were structured around post-structuralism views of identity and aimed to uncover the influence of intercultural encounters on ELTs before, during, and after their summer camp experiences. The study included ten participants who shared their stories of interactions with people from diverse cultural and ethnic backgrounds. The primary objectives of the study were to describe the various types of intercultural encounters that the participants experienced, identify the facilitators and challenges in their learning, explain the impact of these encounters on the participants' perceptions and beliefs, and examine how these encounters contributed to the development of their professional identities. The main findings suggest that intercultural interactions and encounters became identity catalyzers that activated the participants' exploration and construction of their individual and professional identities as language teachers. The study sheds light on the embedded, symbolic, performative, embodied, multilayered, intersectional, intersubjective, and contingent nature of identity. It contributes to understanding the potential of short-term sojourns in transforming future language educators' identities.